B-Comet Assay (Comet Assay on Buccal Cells) for the Evaluation of Primary DNA Damage in Human Biomonitoring Studies - Carla Russo (International Journal of Environmental Research and Public Health, 2020)
Many subjects perceive venous blood collection as too invasive, and thus moving to better-accepted procedures for leukocytes collection might be crucial in human biomonitoring studies (e.g., biomonitoring of occupational or residential exposure to genotoxins) management. In this context, primary DNA damage was assessed in buccal lymphocytes (BLs), fresh whole venous, and capillary blood leukocytes, and compared with that in peripheral blood lymphocytes (PBLs)—the most frequently used cells—in 15 young subjects. Mouthwashes were collected after the volunteers rinsed their mouths with normal saline, and BLs were isolated by density gradient centrifugation. Blood samples were collected by venipuncture or by lancet. Anthropometric and lifestyle information was obtained by the administration of a structured questionnaire. As shown in the Bland-Altman plots, the level of agreement between BLs and PBLs lied within the accepted range, we thus enrolled a wider population (n = 54) to assess baseline DNA damage in BLs. In these cells, mean values of tail length (µm), tail intensity (%), and tail moment were 25.7 ± 0.9, 6.7 ± 0.4 and 1.0 ± 0.1, respectively. No significant association was observed between sex and smoking habit with any of the DNA damage parameters. Conversely, underweight subjects displayed significantly higher genomic instability compared with normal weight group (p < 0.05). In conclusion, we successfully managed to set up and update a non-invasive and well-accepted procedure for the isolation of BLs from saliva that could be useful in upcoming biomonitoring studies.